2022
DOI: 10.4103/ijo.ijo_997_22
|View full text |Cite
|
Sign up to set email alerts
|

Designing and making an open source, 3D-printed, punctal plug with drug delivery system

Abstract: With the advancement in the study of keratoconjunctivitis sicca and the scope of its treatment, punctal plugs are being widely used for the therapeutic management of dry eye disease. With the emergence of 3D printing in medicine, 3D printing of punctal plugs that have an inbuilt drug delivery system and also that can be personalized from patient to patient according to their punctum size can be a great therapeutic option. Another benefit of the device is that its printing takes a short period of time and is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In essence, there exist great opportunities for 3D printing in various non-surgical aspects of ocular disease. However, as of now, the majority remain developmental [ 52 , 53 ] in vivo [ 54 , 55 ], or simply case studies [ 51 , 53 ]. As novel research on the topic of 3D printing in ocular disease continues to emerge, large-scale clinical studies to properly depict the outcomes of such new technology remain important.…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
See 1 more Smart Citation
“…In essence, there exist great opportunities for 3D printing in various non-surgical aspects of ocular disease. However, as of now, the majority remain developmental [ 52 , 53 ] in vivo [ 54 , 55 ], or simply case studies [ 51 , 53 ]. As novel research on the topic of 3D printing in ocular disease continues to emerge, large-scale clinical studies to properly depict the outcomes of such new technology remain important.…”
Section: Applications Of 3d Printing In Oculoplastic and Orbital Surgerymentioning
confidence: 99%
“…Furthermore, this study differentiates itself from others by underlying the fact that a standard, universal apparatus design may sometimes be more beneficial than custom-fitted ones. In dry eye disease, 3D-printed punctal plugs have been studied to treat dry eyes while simultaneously delivering drugs and increasing patient compliance compared to traditional topical drugs [53,54]. Xu et al (2021) studied a 3D-printed drug-loaded punctal plug in vivo, which showed extended release characteristics and the absence of drug-photopolymer interaction when using dexamethasone and polyethylene glycol [54].…”
Section: Use Of Orbital Implants In the Repair Of Orbital Floor Injuriesmentioning
confidence: 99%
“…Back in the days of this work, the definition solely addressed computer software. However, nowadays, the term is much broader and includes additional areas such as open-source hardware [6][7][8], open innovation [8,9], and the increasing use of CAD models in the three-dimensional; (3D) printing community [10,11]. One of the major advantages of the open-source 3D printing community is an economic way of producing individual and customized products, which can lead to the sustainable development of ideas, projects, and, therefore, manufacturable items [4,12].…”
Section: Introductionmentioning
confidence: 99%